THE USE OF SMALL GROUP DISCUSSION METHOD IN TEACHING STUDENTS’ READING COMPREHENSION (ELang | An English Language Education Journal, 2023)
The research paper entitled “The Use of Small Group Discussion Method in Teaching Students’ Reading Comprehension”. The purpose of the study was to know if there is a significant difference between the small group discussion method and the conventional method in teaching reading comprehension to eighth-grade students in Junior High School. This research was conducted at SMP Banjar Asri, located at Jln. Gunung Puntang KM 1. This type of research is quasi-experimental. The population of this research was eight grades of SMP Banjar Asri and the sample was 30 students of VIII B as the experimental class and 30 students of VIII C as the control class. In collecting data, the researcher used a test named pre-test and post-test. This research indicated that the pre-test means score of the experiment class was 58 and the mean score of the control class was 53. After giving treatment, the post-test means score of the experiment class was 75 and the means score of the control class was 60. The result indicated that the students who taught by using the small group discussion method got a higher score than the students who taught by a conventional method. The result of the analysis t-test calculation, where the t-observe is bigger than the t-table. As the derived t = 7.462 exceeds the table critical value of t = 2.000, at p= 0.05 with Df = 58 (7.462 > 2.000). Therefore, the Alternative Hypothesis (Ha) is accepted, stating that there is a significant difference between the small group discussion method and conventional teaching in teaching students reading comprehension in the eighth grade of Junior High School, and the Null Hypothesis (Ho) is rejected. Based on the result above, it can be concluded that the Small Group Discussion Method is effective in improving students’ reading comprehension of narrative text. Then, the result of the data from the questionnaires was almost all of the students answered liked being taught reading comprehension by using the small group discussion method. It was shown by the result of the questionnaire that 90% of the students answered that learning narrative text in reading comprehension through small group discussion is effective. It can be concluded that students’ responses were positive, and good and can improve students’ reading comprehension.Keywords ; SGD, Methode, Reading Comprehension